ANTIMICROBIAL ACTIVITY OF AQUEOUS AND ETHANOLIC LEAF EXTRACTS OF ANACARDIUM OCCIDENTALE - Kl, Shobha; Shobha Rao, Amita; Ksr, Pai; Bhat, Sujatha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to evaluate the antimicrobial activity of leaves of Anacardium occidentale (A. occidentale) against microorganisms including multidrug-resistant (MDR) bacteria. Methods: Agar well diffusion method was employed to demonstrate the antimicrobial activity of leaves A. occidentale. Ethanol and aqueous extracts of the leaves were used against microorganisms, which included American type culture collection strains of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, and Pseudomonas aeruginosa and the clinical isolates of Streptococcus pneumoniae, Candida albicans, MDR Escherichia coli, and MDR Klebsiella pneumoniae. Results: The ethanolic extract of leaves of A. occidentale showed significant antimicrobial activity. Aqueous extract had mild antifungal activity. Conclusion: Ethanolic extract of leaves of A. occidentale could be a good source for the antibacterials to combat MDR bacterial infections. Further studies are necessary for these potent plant extracts to evaluate the in vivo efficacy and toxicity.